Strategies for using voice recordings in the development of English pronunciation - Maldonado León, Kenneth Francisco (2024)
This research work to explore the use of voice recordings in the development of English pronunciation skills. Improving pronunciation requires listening, tone, accent, stress, and native language pronunciation practice to overcome communication barriers, especially for travelers abroad. This research aims to fill this gap in knowledge and provide practical guidance for language learners and educators. This is summarized in the use of data collection techniques in the following paragraph. The survey explored various factors, including the types and frequency of voice recordings such as podcasts and YouTube videos students utilize, and their employed strategies for processing these recordings. Speaking and reading tests were administered to the students to assess their pronunciation skills before and after using voice recordings. The tests were designed to evaluate a range of pronunciation features, including stress, vowel quality, and consonant pronunciation. The results of the study revealed that most students were using voice recordings to improve their pronunciation, to sharpen the ear and for the understanding of native English, but they were not consistently employing the most effective techniques. The study also found that voice recordings can be an effective tool for improving pronunciation, but that individual differences and the quality of the recordings can impact their effectiveness. By conducting this research work, the researchers aim to provide valuable guidance to language learners and educators on the effective use of voice recordings to improve the listening skill before the development of English pronunciation skills. This research could also inform the development of future studies to explore other aspects of pronunciation development, such as the use of feedback mechanisms or the impact of accent and native language on pronunciation learning.